Financialization under state entrepreneurialism in China. Issue 8 (3rd August 2022) - Wu, Fulong; Pan, Fenghua; Chen, Jie
ABSTRACT: This special issue comprehensively researches China's financialization and examines the transformation of its development model, state development corporations, local government bonds, productivity, and the extent and characteristics of financialization. While it is widely known that the state plays an important role in enabling and constraining financialization, these papers further reveal that China's financialization originates from the state's deployment of financial approaches to urban and regional development under state entrepreneurialism. Through internalizing financial logic into the state development system, the expansion of financial operations reflects the state's developmental intention and increases its governance capability. Thus, financialization is not a unidirectional process but involves extensive state involvement and participation in finance, to such an extent that it often simultaneously evolves into greater interference and de-financialization.